1993
DOI: 10.1080/1120009x.1993.11739221
|View full text |Cite
|
Sign up to set email alerts
|

Risk/Benefit in the Treatment of Children with Imipenem-Cilastatin for Meningitis Caused by Penicillin-Resistant Pneumococcus

Abstract: A new case of pneumococcal meningitis in a child successfully treated with imipenem-cilastatin after failure of standard antibiotics is presented. Seizures, as the major adverse effect, were easily treated and no sequelae were later observed. The difficulty in distinguishing between seizures due to meningitis and those due to imipenem is discussed. We conclude that imipenem-cilastatin is a good alternative therapy in children's meningitis caused by pneumococcus resistant to standard antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Adverse events considered related to the study drugs were observed in 14 of 190 patients (5 given meropenem [5.1%] and 9 given cefotaxime [9.8%]). In the meropenem group there were single episodes of thrombocythemia, oral moniliasis, diarrhea, rash, and fever, and in the cefotaxime group, there were episodes of oral moniliasis (6), diarrhea (2), and eosinophilia (1).…”
Section: Resultsmentioning
confidence: 99%
“…Adverse events considered related to the study drugs were observed in 14 of 190 patients (5 given meropenem [5.1%] and 9 given cefotaxime [9.8%]). In the meropenem group there were single episodes of thrombocythemia, oral moniliasis, diarrhea, rash, and fever, and in the cefotaxime group, there were episodes of oral moniliasis (6), diarrhea (2), and eosinophilia (1).…”
Section: Resultsmentioning
confidence: 99%
“…The second case report involved an 18-month-old treated with imipenem/cilastatin at a dose of 100 mg/kg/day after failure of other antibiotics [12]. The authors report a generalized tonic-clonic seizure on day 9 of therapy that ceased when 3 mg of diazepam were administered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, animal studies have shown that when used in conjunction with dexamethasone, vancomycin's penetration into the CSF is decreased even further [21]. While imipenem is an effective alternative for treating penicillin-resistant pneumococcal meningitis, it also carries the risk of seizures, especially in the setting of renal insufficiency [22]. Meropenem has shown some activity against this organism, but further experience is needed before recommendations can be made regarding its routine use in this setting [23].…”
Section: Choice Of Empiric Antibioticsmentioning
confidence: 99%